COMPLIANCE TO LONG-TERM TREATMENT OF CARDIOLOGIC PATIENTS WITH MILD TO MODERATE DEPRESSION: INEFFECTIVENESS OF ANTIDEPRESSIVE THERAPY WITH PIRLINDOL IN RANDOMIZED STUDY - E. V. Strokova; E. A. Naumova; J. G. Shvarts (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate the influence of antidepressant therapy with pirlindol on compliance to the long-term treatment and quality of life in patients with cardiovascular diseases and mild to moderate depression. Material and methods. 61 patients with cardiovascular diseases and mild to moderate depression (according to Beck depression scale) were randomized into two groups. Patients of intervention group received pirlindol, while patients of control group did not receive this drug. Compliance to cardiovascular and antidepressant treatment were estimated in 3 and 6 months. Adverse reactions and patients self-assessment of their well-being and global satisfaction in treatmen were also registered.  Results. 24 (75%), 2 (6%) and 0 patients of intervention group continue pirlindol treatment in 1, 3 and 6 months, respectively. In 3 months of observation patients of intervention group took drugs for cardiovascular diseases more often than these in control group (81% vs 72%, respectively , р<0.05), they also less frequently showed adverse reactions (56% vs 72%, respectively ,p=0.01) and more often — improvement of their well-being (65% vs 50%, respectively , р=0.03). Compliance to cardiovascular therapy did not differ significantly in patients of both groups by the end the study.  Conclusion. Antidepressant therapy with pirlindol did not influence compliance to long-term cardiovascular treatment in patients with cardiovascular diseases and mild to moderate depression, apparently because of low compliance to pirlindol therapy.